Answer:
b=7
Step-by-step explanation:
We want to determine the positive base b in which:
![5_b \cdot 23_b = 151_b](https://tex.z-dn.net/?f=5_b%20%5Ccdot%2023_b%20%3D%20151_b)
The easiest way to approach this is to convert all the numbers to base 10.
![5_b=5Xb^0=5\\23_b =(2Xb^1)+(3Xb^0)=2b+3\\151_b=(1Xb^2)+(5Xb^1)+(1Xb^0)=b^2+5b+1\\Therefore:\\5_b \cdot 23_b = 151_b\\5(2b+3)=b^2+5b+1\\10b+15=b^2+5b+1\\b^2+5b+1-10b-15=0](https://tex.z-dn.net/?f=5_b%3D5Xb%5E0%3D5%5C%5C23_b%20%3D%282Xb%5E1%29%2B%283Xb%5E0%29%3D2b%2B3%5C%5C151_b%3D%281Xb%5E2%29%2B%285Xb%5E1%29%2B%281Xb%5E0%29%3Db%5E2%2B5b%2B1%5C%5CTherefore%3A%5C%5C5_b%20%5Ccdot%2023_b%20%3D%20151_b%5C%5C5%282b%2B3%29%3Db%5E2%2B5b%2B1%5C%5C10b%2B15%3Db%5E2%2B5b%2B1%5C%5Cb%5E2%2B5b%2B1-10b-15%3D0)
![b^2-5b-14=0](https://tex.z-dn.net/?f=b%5E2-5b-14%3D0)
Next, we factorize the resulting expression.
![b^2-5b-14=b^2-7b+2b-14=0\\b(b-7)+2(b-7)=0\\(b-7)(b+2)=0\\b-7=0\: or \: b+2=0\\b=7\: or \: b=-2](https://tex.z-dn.net/?f=b%5E2-5b-14%3Db%5E2-7b%2B2b-14%3D0%5C%5Cb%28b-7%29%2B2%28b-7%29%3D0%5C%5C%28b-7%29%28b%2B2%29%3D0%5C%5Cb-7%3D0%5C%3A%20or%20%5C%3A%20b%2B2%3D0%5C%5Cb%3D7%5C%3A%20or%20%5C%3A%20b%3D-2)
The positive value of b for which the equality hold is 7.
Answer:
The Roman numeral Ⅽ
Step-by-step explanation:
<h2>
Answer: g(f(2)) = 11</h2>
Step-by-step explanation:
g(f(2)) is substituting the value of f(2) for x in g(x). But we must first find f(2).
We know that f (x) = ax² - 12
Since f(3) = 24
⇒ a(3²) - 12 = 24
9 a = 36
a = 4
∴ f(2) = (4)(2²) - 12
= 4
⇒ g(f(2)) = 2(4) + 3
= 11
For the division part:
![\frac{5-4}{4-3 }= \frac{1}{1 }=1](https://tex.z-dn.net/?f=%20%5Cfrac%7B5-4%7D%7B4-3%20%7D%3D%20%5Cfrac%7B1%7D%7B1%20%7D%3D1)
But I think your question differs than this..
Am I right?
as your options do not include 1
Answer:
![\large \boxed{\sf \ \ \ p=-11 \ \ \ }](https://tex.z-dn.net/?f=%5Clarge%20%5Cboxed%7B%5Csf%20%5C%20%5C%20%5C%20p%3D-11%20%5C%20%5C%20%5C%20%7D)
Step-by-step explanation:
Hello,
![\alpha \text{ and } \beta \text{ are the roots of the following equation}](https://tex.z-dn.net/?f=%5Calpha%20%5Ctext%7B%20and%20%7D%20%5Cbeta%20%5Ctext%7B%20are%20the%20roots%20of%20the%20following%20equation%7D)
![2x^2+6x-7=p](https://tex.z-dn.net/?f=2x%5E2%2B6x-7%3Dp)
It means that
![2\alpha^2+6\alpha-7=p \\\\2\beta ^2+6\beta -7=p \\\\](https://tex.z-dn.net/?f=2%5Calpha%5E2%2B6%5Calpha-7%3Dp%20%5C%5C%5C%5C2%5Cbeta%20%5E2%2B6%5Cbeta%20-7%3Dp%20%5C%5C%5C%5C)
And we know that
![\alpha= 2\cdot \beta](https://tex.z-dn.net/?f=%5Calpha%3D%202%5Ccdot%20%5Cbeta)
So we got two equations
![2(2\beta)^2+6\cdot 2 \cdot \beta -7=p \\\\8\beta^2+12\beta -7=p\\\\ and \ 2\beta ^2+6\beta -7=p \ So \\\\\\8\beta^2+12\beta -7 = 2\beta ^2+6\beta -7\\\\6\beta^2+6\beta =0\\\\\beta(\beta+1)=0\\\\ \beta =0 \ or \ \beta=-1](https://tex.z-dn.net/?f=2%282%5Cbeta%29%5E2%2B6%5Ccdot%202%20%5Ccdot%20%5Cbeta%20-7%3Dp%20%5C%5C%5C%5C%3C%3D%3E8%5Cbeta%5E2%2B12%5Cbeta%20-7%3Dp%5C%5C%5C%5C%20and%20%5C%202%5Cbeta%20%5E2%2B6%5Cbeta%20-7%3Dp%20%5C%20So%20%5C%5C%5C%5C%5C%5C8%5Cbeta%5E2%2B12%5Cbeta%20-7%20%3D%202%5Cbeta%20%5E2%2B6%5Cbeta%20-7%5C%5C%5C%5C%3C%3D%3E6%5Cbeta%5E2%2B6%5Cbeta%20%3D0%5C%5C%5C%5C%3C%3D%3E%5Cbeta%28%5Cbeta%2B1%29%3D0%5C%5C%5C%5C%3C%3D%3E%20%5Cbeta%20%3D0%20%5C%20or%20%5C%20%5Cbeta%3D-1)
For ![\beta =0, \ \ \alpha =0, \ \ p = -7](https://tex.z-dn.net/?f=%5Cbeta%20%3D0%2C%20%5C%20%5C%20%5Calpha%20%3D0%2C%20%5C%20%5C%20p%20%3D%20-7)
For ![\beta =-1, \ \ \alpha =-2, \ \ p= 2-6-7=-11, \ p=2*4-12-7=-11](https://tex.z-dn.net/?f=%5Cbeta%20%3D-1%2C%20%5C%20%5C%20%5Calpha%20%3D-2%2C%20%5C%20%5C%20p%3D%202-6-7%3D-11%2C%20%5C%20p%3D2%2A4-12-7%3D-11)
I assume that we are after two different roots so the solution for p is p=-11
b) ![\alpha +2 =-2+2=0 \ and \ \beta+2=-1+2=1](https://tex.z-dn.net/?f=%5Calpha%20%2B2%20%3D-2%2B2%3D0%20%5C%20and%20%5C%20%5Cbeta%2B2%3D-1%2B2%3D1)
So a quadratic equation with the expected roots is
![x(x-1)=x^2-x](https://tex.z-dn.net/?f=x%28x-1%29%3Dx%5E2-x)
Hope this helps.
Do not hesitate if you need further explanation.
Thank you